Kinetic and Thermodynamic Study on the Removal of Methyl Orange From Aqueous Solution by Adsorption onto Camel Thorn Plant - Mogaddasi, F.; Momen Heravi, M.; Bozorgmehr, M.R.; Ardalan, P.; Ardalan, T. (Asian Journal of Chemistry, 2010)
The use of cheap, high efficiency and ecofriendly adsorbent has been studied as an alternative source of activated carbon for the removal of dyes from wastewater. This study investigates the use of activated carbon prepared from Camel thorn plant for the removal of methyl orange dye from aqueous solution. The effect of various experimental parameters such as contact time, temperature, initial dye concentration and dose of adsorbent were studied. The results showed that the adsorption of methyl orange as the amount of adsorbent increased, the percentage of dye removal increased accordingly but it decreased with the increase in initial dye concentration and solution temperature. The adsorption kinetics was found to follow pseudo-second-order rate kinetic model, (R2 > 0.99). Langmuir and Freundlich isotherms were used to analyze the equilibrium data at different temperatures. The apparent thermodynamic parameters were calculated and the adsorption process was found to be spontaneous and exothermic.